NEUROPYCHOLINGUISTICS - THEORY OF BODY STUDY - Bobokalonov Ramazon Rajabovich (Modern American Journals, 2025)
The article analyzes neuropsycholinguistic situations related to the human body and body movements within the framework of modern requirements. Attention to human health and the causes of speech disorders are explained.
Keywords: Dopamine, neurotransmitter, adrenaline, noradrenaline, serotonin, oxytocin, vasopressin, noradrenaline, melatonin, gamma-aminobutyric acid, prefrontal cortex, insula, amygdala, cingulate cortex, cortisol.